Experiences of Iranian female patients with systemic lupus erythematosus: A qualitative study - Zahra Behboodi MOGHADAM,; Seyedeh Tahereh FAEZI,; Armin ZAREIAN,; Elham REZAEI, (Archives of Rheumatology, 2021)
Objectives: This study aims to explore the perceptions, concerns, expectations, and viewpoints of female patients with systemic lupus erythematosus (SLE) regarding reproductive health in Iran. Patients and methods: This qualitative research was conducted using 27 semi-structured deep interviews with 19 married female patients (mean age 37.4±7.0 years; range, 15 to 49 years) suffering from SLE selected through purposive sampling in the Rheumatology Center of Shariati Hospital, Tehran, Iran between August 2017 and March 2018. Results: Patients’ perceptions were classified into six categories and 14 subcategories: physical suffering (debilitating pain, gradual disability, and apparent transformation), psychological stress (family disturbance and sexual dissatisfaction), challenging fertility (bothersome pregnancy and impaired parenting), adaptation to the disease (self-care and lifestyle modification), need for a supporter (support from the spouse, support from the family and acquaintances, and lack of occupational and social support), and spirituality (forgiveness of sins and resorting to God). Conclusion: The findings clearly suggested the negative effects of SLE on the reproductive health of these patients. This study emphasized the importance of care and support for female patients with SLE. We hope that this research enhances the awareness of care providers about physical, sexual, psychological, social, and spiritual factors, since taking care of these patients requires strategic and multidisciplinary management.